Diagnostic Utility of Bronchoalveolar Lavage and Bronchial Brush Cytology in Lung Lesions - George, Jofy; T, Umashankar (Annals of Pathology and Laboratory Medicine, 2020)
Background: In 1960’s, flexible fiberoptic bronchoscope, was first used to give a better yield to diagnose pulmonary diseases. Bronchial brushing cytology (BBC) and Broncho-alveolar lavage (BAL) are two important adjuncts done along with bronchoscopic biopsy. Bronchial brushings yield better diagnostic material than simple exfoliative cytology. Therefore, both techniques are of much diagnostic value and is widely accepted as it is safe, economical and evaluation requires much less time. Methods: All the bronchial brush and bronchoalveolar lavage smears obtained from January 2018 to December 2018 were assessed. Correlation was done with histopathology wherever was available. Result: BBC showed a sensitivity and specificity of 59.28% and 100%. The positive predictive value and negative predictive value were 100% and 47.62%. BAL showed a sensitivity and specificity of 51% and 100%. The positive predictive value and negative predictive value was 100% and 43.18%. The diagnostic accuracy of BBC and BAL were 70.27% and 64.86%. Conclusion: Universally bronchial washings and bronchial brushings should be considered important adjunct to bronchoscopic biopsies to diagnose pulmonary lesions as both are safe, economical and can will give better diagnostic yield if incorporated together.